Assessing how rural-urban migration is incorporated in Ghana's national urban policy: a qualitative content analysis. Issue 12 (2nd December 2022) - Kutor, Senanu Kwasi; Annan-Aggrey, Eunice; Poku, Adjoa Afriyie; Kyeremeh, Emmanuel; Arku, Godwin
ABSTRACT: Urbanisation is increasingly recognised as one of the pressing global issues. As a result, managing contemporary and future urban processes to produce sustainable outcomes has become a preoccupation of policy analysts, academics, and urban planners. Urbanisation can either produce positive or negative outcomes depending on how authorities and stakeholders at all levels manage it. In African context, several national governments have formulated and implemented National Urban Policies (NUPs) as a way of curbing urban challenges associated with urbanisation. This paper provides a content analysis of Ghana's NUP. The objective of this paper is two-fold: to evaluate the (a) dominant themes that are covered in Ghana's NUP and why the emphasis on those themes; and (b) the extent to which rural–urban migration is factored into the policy document. The latter is more critical because in Africa's context, besides natural population increase and reclassification of rural settlements as urban areas, rural–urban migration is one of the fundamental drivers of urbanisation. Our analyses revealed that the dimension of rural–urban migration is ignored in the policy document. This neglect, we argue, is problematic because rural–urban migration is one of the drivers of urbanisation in Ghana. Policy recommendations, including the need to minimise the push and pull causes of rural–urban migration, the need to give proper meaning to the decentralisation concept, and the need for the government to focus on rural development interventions are proffered to strengthen the overall goal of Ghana's NUP in the context of urbanisation.